PENGARUH KUALITAS PELAYANAN DAN HARGA TIKET KERETA API TERHADAP LOYALITAS PELANGGAN JASA KERETA API INDONESIA (Studi Pada Kereta Api Argo Muria Kelas Eksekutif Jurusan Semarang Tawang – Jakarta Gambir PT Kereta Api Indonesia DAOP 4 Semarang) - Ramadhan, Hilmy; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2019)
This study aims to determine the effect of service quality and ticket prices on customer loyalty. This type of research uses the type of explanatory research. The sampling technique uses purposive sampling technique. The population of this study is the Argo Muria train passengers as many as 100 respondents. This study uses quantitative analysis with validity, reliability, correlation coefficient, determination coefficient, simple regression, multiple regression, t test and F test with the help of Microsoft Excel and SPSS version 21. The results showed that it could be concluded that t arithmetic (6.339)> t table (1.984), then Ho was rejected and Ha was accepted. There is a significant influence between Service Quality on Customer Loyalty. then t calculate the ticket price to customer loyalty (7,823)> t table (1,984), then Ho is rejected and Ha is accepted. There is a significant influence between Price on Customer Loyalty. Then F-count service quality and price to customer loyalty is (35,704)> F-table (3.09) which means that Ho is rejected and Ha is accepted. Testing this hypothesis proves that together - positive and significant effect between Service Quality and Ticket Prices on Customer Loyalty of Argo Muria Railroad Services PT. KAI DAOP 4 Semarang.